(untitled) (MAUSAM, 1986)
The present investigation represents the theoretical study of storm surge problem on a continental shelf, This problem is found to happen on the coastal bed due to a disturbance, such as storm, generated in the deep sea. In studying the present problem the coastal geometry consists of a vertical straight wall extending to infinity in horizontal direction with sloping bottom, In this analysis the linear model of the system of equations has been considered; the effects of coriolis parameter and bottom friction have also been taken into account, The main result obtained in this theoretical investigation is the analytical expression for the sea surface elevation on the continental bed.